Multi-processor system-on-chip. - Andrade, Liliana; Rousseau, Frédéric, 1967- (ISTE, Ltd. ; Wiley, 2021)
A Multi-Processor System-on-Chip (MPSoC) is the key component for complex applications. These applications put huge pressure on memory, communication devices and computing units. This book, presented in two volumes - Architectures and Applications - therefore celebrates the 20th anniversary of MPSoC, an interdisciplinary forum that focuses on multi-core and multi-processor hardware and software systems. It is this interdisciplinarity which has led to MPSoC bringing together experts in these fields from around the world, over the last two decades.